Palm Sugar Agribusiness Development Strategy In Tasikmalaya Regency - Candra Nuraini; Unang Atmaja (Agriekonomika, 2019)
Sugar palm (Arenga Pinnata, MERR) is one of the most valuable commodities in the plantation sector; thus, they have enormous potential to be developed. The agribusiness development of sugar palm should start from the upstream to the downstream. Therefore, a study on the strategies to develop agribusiness of palm sugar is necessary to be conducted. This research is conducted to: 1) identify the internal and external factors, 2) formulate palm sugar agribusiness development strategies, and 3) determine the priority of palm sugar agribusiness development strategies.The method employed in this research is descriptive qualitative approach. The research area, Tasikmalaya regency, is chosen using the purposive sampling. The method used to collect the data is non probability sampling (Non-random). The analysis applied here are SWOT and AHP. The result shows that the priority orders of strategies are: (1) Cultivation development with certified parent stocks (0,3); (2) The institutional arrangements of agribusiness system by involving the relations with the stakeholder (0,27); (3) The assistance provisions to the facilities and infrastructures of the processing (0,14); (4) strengthening of product diversification and packaging innovation (0,13); (5) the Technology Development with the value 0,09; and (6) the improvement of marketing mechanism and market information with the value 0,07. The results of the study suggest that the strategic priority is the development of certified parent seed cultivation.